Study on solid state reactions of nanocrystalline Cu–Ge alloys upon mechanical alloying and annealing. (April 2014) - Nazarian-Samani, Mahboobeh; Reza Kamali, Ali; Nazarian-Samani, Masoud
Abstract : The structural evolution of Cu–12 wt·%Ge (∼Cu–11 at·%Ge) alloy processed by means of mechanical alloying (MA) with subsequent heat treatment was studied using X-ray diffraction profiles, scanning electron microscopy, transmission electron microscopy (TEM) and high resolution TEM observations as well as differential thermal analysis(DTA). The fcc Cu(Ge) solid solution ( α ) was produced at early stages of MA and amorphised upon further milling. This was followed by the formation of ζ−Cu5 Ge intermetallic nanocrystals after 40 h of milling. The subsequent annealing process led to the nanocrystallisation of the amorphous powder. The X-ray crystallite size data showed the exceptional thermal stability of the alloy prepared. The mechanism of the stability was also investigated. In addition, a thermodynamic analysis based on Miedema's semiempirical model was carried out for the evaluation of the experimental results and a good agreement was found between them.